Tax in the Digital Age: A Systematic Study on E-commerce and Taxation Policy - Putri, Ayu Fitria; Prasetyawati, Tyas; Mukhtaruddin, Mukhtaruddin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to analyze taxation policies in the digital era, particularly in the e-commerce sector, using a literature review approach based on 22 academic journals. The findings indicate that the most frequently used theories in e-commerce taxation research are the Tax Compliance Theory and Tax Awareness Theory, each cited in five journals. Additionally, qualitative research methods dominate at 38.1%, while quantitative methods account for 61.9% of the studies. Key factors influencing tax compliance in e-commerce include tax understanding and awareness, sanctions and law enforcement, trust in tax authorities, tax socialization, and tax regulations and policies. The proposed policy implications include enhancing education and socialization, strengthening regulatory frameworks and legal certainty, implementing tax incentives, and optimizing oversight and sanctions. This study highlights the necessity for taxation policies in the digital era to continuously adapt to improve compliance and create a fair and effective system for e-commerce businesses.